Mycorrhizal lipochitinoligosaccharides (LCOs) depolarize root hairs of Medicago truncatula - Hürter, Anna-Lena (PLoS One, 2018)
Arbuscular Mycorrhiza and Root Nodule Symbiosis are symbiotic interactions with a high benefit for plant growth and crop production. Thus, it is of great interest to understand the developmental process of these symbioses in detail. We analysed very early symbiotic responses of Medicago truncatula root hair cells, by stimulation with lipochitinoligosaccharides specific for the induction of nodules (Nod-LCOs), or the interaction with mycorrhiza (Myc-LCOs). Intracellular micro electrodes were used, in combination with Ca(2+) sensitive reporter dyes, to study the relations between cytosolic Ca(2+) signals and membrane potential changes. We found that sulfated Myc- as well as Nod-LCOs initiate a membrane depolarization, which depends on the chemical composition of these signaling molecules, as well as the genotype of the plants that were studied. A successive application of sulfated Myc-LCOs and Nod-LCOs resulted only in a single transient depolarization, indicating that Myc-LCOs can repress plasma membrane responses to Nod-LCOs. In contrast to current models, the Nod-LCO-induced depolarization precedes changes in the cytosolic Ca(2+) level of root hair cells. The Nod-LCO induced membrane depolarization thus is most likely independent of cytosolic Ca(2+) signals and nuclear Ca(2+) spiking.